The Effectiveness of Cervical Medial Branch Radiofrequency Ablation for Chronic Facet Joint Syndrome in Patients Selected by a Practical Medial Branch Block Paradigm. Issue 10 (5th February 2020) - Burnham, Taylor; Conger, Aaron; Salazar, Fabio; Petersen, Russell; Kendall, Richard; Cunningham, Shellie; Teramoto, Masaru; McCormick, Zachary L
Abstract: Background: Cervical medial branch radiofrequency ablation (CMBRFA) is an effective treatment for facetogenic pain in patients selected by Spine Intervention Society (SIS) guidelines of 100% symptom improvement with dual medial branch blocks (MBBs) ± placebo block. Patient selection for CMBRFA using ≥80% symptom improvement after dual concordant MBBs is common; however, this has not been studied. Objective: To evaluate the effectiveness of CMBRFA and compare outcomes in individuals selected by 80–99% vs 100% symptom improvement with dual concordant MBBs. Design: Cross-sectional cohort study. Methods: Medical records of 87 consecutive patients were reviewed; 50 met inclusion criteria. A standardized telephone survey was performed at six or more months post-CMBRFA to query numerical rating scale (NRS) pain and patient global impression of change (PGIC) scores. The primary outcomes were the proportion of patients reporting ≥50% reduction of index pain. Results: At a mean follow-up time of 16.9 ± 12.7 months, 54% (95% confidence interval [CI] = 35–73%) and 54% (95% CI = 32–74%) of the 80–99% and 100% MBBs groups, respectively, reported ≥50% pain reduction. Between-group comparison showed a relative risk of 0.99 (95% CI = 0.59–1.66) for meeting the primary outcome. Seventy percent (95% CI = 56–81%) of patients reported a PGIC score consistent with "improved or very much improved" at follow-up. Conclusions: CMBRFA is an effective treatment in patients who report ≥80% symptom relief with dual concordant MBBs. The present study demonstrated an overall ≥50% pain reduction rate of 54% and no significant difference between those selected by 80–99% vs 100% symptom relief with dual concordant MBBs.